Phosphorus sulfide composition for sulfide-based inorganic solid electrolyte material, method for producing sulfide-based inorganic solid electrolyte material, and method for managing quality of phosphorus sulfide composition

By using a highly reactive phosphorus sulfide composition for mechanical and heat treatment, a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity was prepared, which solved the complex manufacturing process in the prior art and achieved improvement in material performance.

CN119678224APending Publication Date: 2025-03-21FURUKAWA COMPANY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380058773.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-10
Filing Date
2023-07-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing sulfide inorganic solid electrolyte materials require vacuum sealing during the manufacturing process, which is complex and has room for improvement.

Method used

By using a phosphorus sulfide composition with a reactive property of 5.0°C/min or above as a raw material, mechanical treatment and heat treatment were performed to prepare a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity.

Benefits of technology

The process without vacuum sealing is realized, the lithium ion conductivity is improved, and the manufacturing efficiency and safety of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119678224A_ABST
    Figure CN119678224A_ABST
Patent Text Reader

Abstract

A phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, the phosphorus sulfide composition having a reactivity of 5.0 DEG C / min or more as measured by a predetermined method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, a method for producing the sulfide-based inorganic solid electrolyte material, and a method for quality management of the phosphorus sulfide composition. Background Art

[0002] In the past, lithium-ion batteries used electrolytes containing flammable organic solvents. From the perspective of further improving safety, lithium-ion batteries that replace electrolytes with solid electrolytes and make the batteries fully solid are being developed. In addition, since flammable organic solvents are not required, safety devices are simplified, and manufacturing costs and productivity are excellent.

[0003] As a solid electrolyte material used for such a solid electrolyte, for example, a sulfide-based inorganic solid electrolyte material is known.

[0004] Sulfide-based inorganic solid electrolyte materials are required to have high lithium ion conductivity so as to be able to cope with large current charge and discharge.

[0005] For example, Patent Document 1 discloses a Li-PS-based sulfide-based inorganic solid electrolyte material having high lithium ion conductivity.

[0006] Specifically, a sulfide solid electrolyte material is disclosed, characterized in that the sulfide solid electrolyte material contains Li element, P element and S element, and has peaks at positions of 2θ=17.90±0.20°, 29.0±0.50° and 29.75±0.25° in a powder X-ray diffraction measurement using Cu-Kα rays with an X-ray wavelength of 1.5418 angstroms, and the diffraction intensity of the peak at 2θ=17.90±0.20° is set to I A The diffraction intensity of the peak at 2θ = 18.50 ± 0.20° is defined as I B In this case, I B / I A The value is less than 0.50; it has the following crystalline structure: it includes a plurality of PS4 tetrahedrons, each PS4 tetrahedron is arranged in a manner where the vertices of the PS4 tetrahedron are oriented differently from each other, and the PS4 tetrahedrons do not share edges, and, in the lattice constant determined by diffraction measurement, the ratio of the maximum axial length to the minimum axial length is less than 1.1; the diffraction intensity of the peak at 2θ=29.0±0.50° is smaller than the diffraction intensity of the peak at 2θ=29.75±0.25°.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent document 1: Japanese Patent No. 6861869. Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, the sulfide inorganic solid electrolyte material disclosed in Patent Document 1 requires a complicated process of vacuum sealing during production, and there is room for improvement in this regard.

[0012] The present inventors have conducted intensive research on the production of sulfide-based inorganic solid electrolyte materials. As a result, they have found that by evaluating and sorting the phosphorus sulfide composition, which is the raw material of the sulfide-based inorganic solid electrolyte material, using the index of "reactivity", a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity can be obtained without the need for a vacuum sealing step, thereby completing the present invention.

[0013] The present invention has been made in view of the above circumstances, and provides a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material capable of producing a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity, a method for producing a sulfide-based inorganic solid electrolyte material capable of producing a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity, and a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity.

[0014] Means for solving problems

[0015] The present inventors have completed the invention provided below and solved the above-mentioned problems.

[0016] 1. A phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, wherein the phosphorus sulfide composition has a reactivity of 5.0°C / min or more as measured by the following [Method 1].

[0017] [Method 1]

[0018] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0019] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0020] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0021] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0022] The reactivity is derived from the following formula (1).

[0023] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0024] 2. The phosphorus sulfide composition according to 1, wherein the phosphorus sulfide composition contains P2S5.

[0025] 3. The phosphorus sulfide composition according to 2, wherein the content of P2S5 in the phosphorus sulfide composition is 95% by mass or more.

[0026] 4. The phosphorus sulfide composition according to any one of 1 to 3, which is in a powdery form.

[0027] 5. A raw material composition for a sulfide-based inorganic solid electrolyte material, comprising the phosphorus sulfide composition according to any one of 1 to 4 and lithium sulfide.

[0028] 6. A method for producing a sulfide-based inorganic solid electrolyte material, comprising the step of mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material according to 5.

[0029] 7. A sulfide-based inorganic solid electrolyte material, wherein the sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained using the phosphorus sulfide composition according to any one of 1 to 4 as a raw material.

[0030] 8. A sulfide-based inorganic solid electrolyte, wherein the sulfide-based inorganic solid electrolyte comprises the sulfide-based inorganic solid electrolyte material according to 7.

[0031] 9. A sulfide-based inorganic solid electrolyte membrane, comprising the sulfide-based inorganic solid electrolyte according to 8 as a main component.

[0032] 10. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer comprises the sulfide-based inorganic solid electrolyte material described in 7.

[0033] 11. A method for producing a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, comprising the step of sorting a phosphorus sulfide composition having a reactivity of 5.0°C / min or more measured by the following [Method 1].

[0034] [Method 1]

[0035] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0036] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0037] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0038] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0039] The reactivity is derived from the following formula (1).

[0040] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0041] 12. A quality control method for a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, comprising the step of judging as acceptable a phosphorus sulfide composition having a reactivity of 5.0°C / min or more as measured by the following [Method 1].

[0042] [Method 1]

[0043] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0044] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0045] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0046] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0047] The reactivity is derived from the following formula (1).

[0048] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0049] 13. A method for producing a sulfide-based inorganic solid electrolyte material, wherein the method comprises: a step of mixing a raw material composition containing lithium sulfide and the phosphorus sulfide composition described in any one of 1 to 4 to obtain a mixture; and a step of subjecting the obtained mixture to a mechanochemical treatment to obtain a mechanochemically treated product.

[0050] [Method 1]

[0051] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0052] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0053] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0054] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0055] The reactivity is derived from the following formula (1).

[0056] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0057] 14. The method for producing a sulfide-based inorganic solid electrolyte material according to 13, further comprising the step of heat-treating the mechanochemically treated product at a temperature in the range of 180°C to less than 450°C.

[0058] 15. The method for producing a sulfide-based inorganic solid electrolyte material according to 13 or 14, wherein the method does not include a step of heating the mechanochemically treated product at 450° C. or higher.

[0059] 16. The method for producing a sulfide-based inorganic solid electrolyte material according to any one of 13 to 15, wherein the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in the following <Measurement of lithium ion conductivity> is 1.0×10 -3 S / cm or more.

[0060] <Measurement of lithium ion conductivity>

[0061] First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1 mm.

[0062] Then, the lithium ion conductivity of the obtained disk-shaped sample was measured by an electrochemical measuring apparatus under the conditions of an applied voltage of 10 mV, a measuring frequency range of 0.1 Hz to 3 MHz, and a measuring temperature of 27° C., using a Li foil as an electrode, and an AC impedance method.

[0063] 17. The method for producing a sulfide-based inorganic solid electrolyte material according to any one of 13 to 16, wherein the oxidative decomposition current value of the sulfide-based inorganic solid electrolyte material measured by the method described in the following <Measurement of the maximum value of oxidative decomposition current> is 0.10×10 -5 mA or less.

[0064] <Determination of the maximum value of the oxidative decomposition current>

[0065] First, 150 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1.3 mm.

[0066] Then, a Li foil as a reference electrode / counter electrode was pressure-bonded to one surface of the obtained disk-shaped sample under the conditions of 18 MPa for 10 minutes, and then a SUS314 foil as a working electrode was attached to the other surface facing upward.

[0067] Then, using an electrochemical measuring apparatus, the maximum value of the oxidative decomposition current of the obtained particles was measured under the conditions of a sweep voltage range of 0 to 10 V, a voltage sweep rate of 5 mV / sec, and a measurement temperature of 25°C.

[0068] 18. A method for producing a sulfide-based inorganic solid electrolyte material as described in any one of 13 to 17, wherein, in the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material obtained by the method described in the following <X-ray diffraction analysis>, there is no peak in the range of 2θ=27.70±0.50°, there is a peak in the range of 2θ=17.90±0.20°, there is a peak in the range of 2θ=29.00±0.50°, and there is a peak in the range of 2θ=29.75±0.25°.

[0069] <X-ray diffraction analysis>

[0070] An X-ray diffraction apparatus was used, with a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a divergence slit longitudinal limit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, and a measurement end angle of 90°. CuKα rays were used as the ray source to obtain an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material.

[0071] 19. The method for producing a sulfide-based inorganic solid electrolyte material according to any one of 13 to 18, wherein the sulfide-based inorganic solid electrolyte material contains Li3PS4.

[0072] 20. The method for producing a sulfide-based inorganic solid electrolyte material as described in 19, wherein the Li3PS4 is α-type Li3PS4.

[0073] 21. A sulfide-based inorganic solid electrolyte material, wherein the sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained by the method for producing a sulfide-based inorganic solid electrolyte material according to any one of 13 to 20.

[0074] 22. A sulfide-based inorganic solid electrolyte, wherein the sulfide-based inorganic solid electrolyte comprises the sulfide-based inorganic solid electrolyte material according to 21.

[0075] 23. A sulfide-based inorganic solid electrolyte membrane, comprising the sulfide-based inorganic solid electrolyte according to 22 as a main component.

[0076] 24. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer comprises the sulfide-based inorganic solid electrolyte material described in 21.

[0077] 25. A sulfide-based inorganic solid electrolyte material, which is a sulfide-based inorganic solid electrolyte material containing Li, P and S as constituent elements, wherein, in an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material obtained by the method described in the following <X-ray diffraction analysis>, there is no peak in the range of 2θ=27.70±0.50°, there is a peak in the range of 2θ=17.90±0.20°, there is a peak in the range of 2θ=29.00±0.50°, and there is a peak in the range of 2θ=29.75±0.25°.

[0078] <X-ray diffraction analysis>

[0079] An X-ray diffraction apparatus was used with a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a divergence slit longitudinal limit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, and a measurement end angle of 90°. CuKα rays were used as the ray source. In addition, a glass sample plate was used as the sample holder to obtain an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material.

[0080] 26. The sulfide-based inorganic solid electrolyte material as described in 25, wherein the sulfide-based inorganic solid electrolyte material contains Li3PS4.

[0081] 27. The sulfide-based inorganic solid electrolyte material according to 26, wherein the content of Li3PS4 is greater than 95% by mass.

[0082] 28. The sulfide-based inorganic solid electrolyte material according to any one of 25 to 27, wherein the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in the following <Measurement of lithium ion conductivity> is 1.0×10 -3 S / cm or more.

[0083] <Measurement of lithium ion conductivity>

[0084] First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1 mm.

[0085] Then, the lithium ion conductivity of the obtained disk-shaped sample was measured by an electrochemical measuring apparatus under the conditions of an applied voltage of 10 mV, a measuring frequency range of 0.1 Hz to 3 MHz, and a measuring temperature of 27° C., using a Li foil as an electrode, and an AC impedance method.

[0086] 29. The sulfide-based inorganic solid electrolyte material according to any one of 25 to 28, wherein the oxidation decomposition current value of the sulfide-based inorganic solid electrolyte material measured by the method described in the following <Measurement of the maximum value of oxidation decomposition current> is 0.10×10 -5 mA or less.

[0087] <Determination of the maximum value of the oxidative decomposition current>

[0088] First, 150 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1.3 mm.

[0089] Then, a Li foil as a reference electrode / counter electrode was pressure-bonded to one surface of the obtained disk-shaped sample under the conditions of 18 MPa for 10 minutes, and then a SUS314 foil as a working electrode was attached to the other surface facing upward.

[0090] Then, using an electrochemical measuring apparatus, the maximum value of the oxidative decomposition current of the obtained particles was measured under the conditions of a sweep voltage range of 0 to 10 V, a voltage sweep rate of 5 mV / sec, and a measurement temperature of 25°C.

[0091] 30. A sulfide-based inorganic solid electrolyte, comprising the sulfide-based inorganic solid electrolyte material according to any one of 25 to 29.

[0092] 31. A sulfide-based inorganic solid electrolyte membrane, comprising the sulfide-based inorganic solid electrolyte according to 30 as a main component.

[0093] 32. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer comprises the sulfide-based inorganic solid electrolyte material described in any one of 25 to 29.

[0094] Effects of the Invention

[0095] According to the present invention, a phosphorus sulfide composition capable of preparing a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity, a method for producing a sulfide-based inorganic solid electrolyte material capable of preparing a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity, and a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity are provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0096] Figure 1 It is a cross-sectional view showing an example of the structure of the lithium ion battery according to the present embodiment.

[0097] Figure 2 It is a diagram showing X-ray diffraction analysis spectra of sulfide-based inorganic solid electrolyte materials obtained in Examples and Comparative Examples.

[0098] Figure 3 This is a diagram showing an enlarged view of the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material obtained in Examples and Comparative Examples in the range of 2θ=10 to 35°. DETAILED DESCRIPTION

[0099] Hereinafter, the present invention will be described based on embodiments.

[0100] 1. First Implementation

[0101] Hereinafter, a first embodiment of the present invention will be described.

[0102] [Phosphorus sulfide composition for sulfide-based inorganic solid electrolyte material]

[0103] The phosphorus sulfide composition for sulfide-based inorganic solid electrolyte material of the present embodiment has a reactivity measured by the following [Method 1] of 5.0°C / min or more, preferably 6.0°C / min or more, more preferably 6.5°C / min or more, further preferably 6.8°C / min or more, further preferably 7.0°C / min or more, further preferably 7.5°C / min or more, further preferably 8.0°C / min or more. The upper limit of the reactivity is not particularly limited, and is, for example, 30.0°C / min or less, 15.0°C / min or less, 10.0°C / min or less, or 9.0°C / min or less.

[0104] [Method 1]

[0105] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0106] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0107] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0108] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0109] The reactivity is derived from the following formula (1).

[0110] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0111] As shown in the following reaction formula (1A), reactivity is an index indicating the amount of heat generated when an alcohol (ROH (R is an arbitrary organic group)) reacts with phosphorus pentasulfide (P2S5) to generate thiophosphoric acid ((RO)2P(S)SH).

[0112] 4ROH+P2S5→2(RO)2P(S)SH+H2S(1A)

[0113] Reactivity is an index used to monitor the amount of heat generated when industrially producing thiophosphoric acid used as a raw material for pesticides, etc., to prevent excessive heat generation and enable stable production. Therefore, in the field of phosphorus sulfide compositions for sulfide-based inorganic solid electrolyte materials, no attention has been paid to the index of reactivity.

[0114] However, the present inventors have found that by evaluating and sorting phosphorus sulfide compositions for sulfide-based inorganic solid electrolyte materials using reactivity as an index, a sulfide solid electrolyte material having improved lithium ion conductivity can be obtained, thereby completing the present invention.

[0115] It should be noted that, as a general theory, the value of the reactivity can be changed by controlling the cooling rate when phosphorus pentasulfide is crystallized.

[0116] The phosphorus sulfide composition of the present embodiment may contain various phosphorus sulfides such as P2S5, P4S3, and P4S7.

[0117] The phosphorus sulfide composition of this embodiment preferably contains P2S5.

[0118] The content of P2S5 in the phosphorus sulfide composition of the present embodiment is preferably 95% by mass or more, more preferably 97% by mass or more, further preferably 99% by mass or more, for example, 100% by mass or less.

[0119] The phosphorus sulfide composition of the present embodiment is preferably in a powdered form. The production of the sulfide-based inorganic solid electrolyte material described below is generally carried out in a dry process, and therefore, the sulfide-based inorganic solid electrolyte material can be produced more easily by making it in a powdered form.

[0120] [Raw material composition of sulfide-based inorganic solid electrolyte material]

[0121] The raw material composition of the sulfide-based inorganic solid electrolyte material of the present embodiment contains the above-mentioned phosphorus sulfide composition of the present embodiment and lithium sulfide.

[0122] For example, the sulfide-based inorganic solid electrolyte material can be obtained by subjecting the above-mentioned raw material composition to mechanical treatment such as mechanochemical treatment.

[0123] The lithium sulfide in the raw material composition is not particularly limited, and commercially available lithium sulfide may be used. For example, lithium sulfide obtained by a reaction between lithium hydroxide and hydrogen sulfide may be used.

[0124] From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and suppressing side reactions, it is preferred to use lithium sulfide having a small amount of impurities.

[0125] Here, in the present embodiment, lithium sulfide also includes lithium polysulfide.

[0126] The raw material composition may contain lithium nitride. Here, since nitrogen in lithium nitride is discharged into the system in the form of N2, by using lithium nitride as a raw material, only the Li composition can be increased for the sulfide-based inorganic solid electrolyte material containing Li, P and S as constituent elements.

[0127] The lithium nitride of this embodiment is not particularly limited, and commercially available lithium nitride (eg, Li3N, etc.) can be used. For example, lithium nitride obtained by the reaction of metallic lithium (eg, Li foil) and nitrogen gas can be used.

[0128] From the viewpoint of obtaining a high-purity solid electrolyte material and suppressing side reactions, it is preferred to use lithium nitride having a small amount of impurities.

[0129] Here, the ratio of each raw material in the raw material composition can be adjusted so that the sulfide-based inorganic solid electrolyte material has a desired composition ratio.

[0130] [Method for producing sulfide-based inorganic solid electrolyte material]

[0131] The method for producing the sulfide-based inorganic solid electrolyte material of the present embodiment includes the step of mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material of the present embodiment described above.

[0132] The method for producing a sulfide-based inorganic solid electrolyte material of the present embodiment includes, for example, the following steps (A) and (B), and may further include steps (C) and (D). Step (D) may be performed after step (B) or after step (C).

[0133] Step (A): A step of mixing a raw material composition of a sulfide-based inorganic solid electrolyte material containing lithium sulfide and the phosphorus sulfide composition of the first embodiment to obtain a mixture.

[0134] Step (B): a step of subjecting the obtained mixture to a mechanical treatment (preferably a mechanochemical treatment) to obtain a glassy sulfide-based inorganic solid electrolyte material (for example, a mechanochemically treated product).

[0135] Step (C): a step of heating the obtained glass-state sulfide-based inorganic solid electrolyte material to crystallize at least a portion thereof, thereby obtaining a glass-ceramic-state sulfide-based inorganic solid electrolyte material.

[0136] Step (D): A step of pulverizing, classifying or granulating the obtained sulfide-based inorganic solid electrolyte material in a glass or glass ceramic state to obtain a sulfide-based inorganic solid electrolyte material.

[0137] In the step (A), a raw material composition of a sulfide-based inorganic solid electrolyte material is mixed to obtain a mixture.

[0138] The mixing method in step (A) is not particularly limited as long as it is a mixing method that can uniformly mix the raw materials. For example, mixing can be performed using a mortar, a ball mill, a bead mill, a vibration mill, a percussion pulverizer, a mixer (a pug mixer, a ribbon mixer, a drum mixer, a tumble mixer, a V-type mixer, etc.), a kneader, a twin-screw kneader, a jet mill, a crusher, a rotary knife type pulverizer, etc.

[0139] The mixing conditions such as the stirring speed, the processing time, the temperature, the reaction pressure, the gravitational acceleration applied to the mixture when mixing the raw materials can be appropriately determined according to the processing amount of the mixture.

[0140] In step (B), the mixture is subjected to a mechanical treatment (preferably a mechanochemical treatment) to obtain a glassy sulfide-based inorganic solid electrolyte material.

[0141] Here, the mechanical treatment refers to a treatment in which two or more inorganic compounds are mechanically collided to cause a chemical reaction and vitrify the inorganic composition, and examples thereof include mechanochemical treatment.

[0142] Here, mechanochemical treatment refers to a method of vitrifying a mixed object while applying mechanical energy such as shear force, collision force or centrifugal force. As an apparatus for vitrifying by mechanochemical treatment, there can be cited pulverizers / dispersers such as ball mills, bead mills, vibration mills, turbine grinders, mechanical fusion machines, and disc mills; and impact crushing devices represented by rock drills, vibration drills, impact drivers, etc., which are composed of a mechanism combining rotation, extrusion, and impact.

[0143] When mechanochemical treatment is used, each raw material can be ground into fine particles and mixed at the same time, thereby increasing the contact area of ​​each raw material, thereby promoting the reaction of each raw material and obtaining a sulfide-based inorganic solid electrolyte material more efficiently.

[0144] The mechanochemical treatment in step (B) is preferably a dry mechanochemical treatment from the viewpoint of easily achieving an environment in which moisture and oxygen are removed at a high level.

[0145] As devices for performing the mechanical treatment in step (B), there can be cited crushing / dispersing machines such as ball mills, bead mills, vibration mills, turbine grinders, mechanical fusion machines, disc mills, and roller mills; rotating / impact crushing devices composed of a mechanism combining rotation (shear stress) and impact (compression stress) such as rock drills, vibration drills, and impact drivers; high-pressure grinding rollers; vertical mills such as roller vertical mills and ball vertical mills, etc.

[0146] Among them, a ball mill and a bead mill are preferred, and a ball mill is more preferred, from the viewpoint of being able to efficiently generate very high impact energy.

[0147] In addition, from the viewpoint of excellent continuous productivity, preferred are roller mills; rotary / impact crushing devices composed of a mechanism combining rotation (shear stress) and impact (compression stress), such as rock drills, vibration drills, and impact drills; high-pressure grinding rollers; vertical mills such as roller vertical mills and ball vertical mills, etc.

[0148] The mixing conditions of the mechanical treatment in step (B), such as the rotation speed, treatment time, temperature, reaction pressure, and gravitational acceleration applied to the raw material composition, can be appropriately determined according to the type and treatment amount of the raw material composition. Generally, the faster the rotation speed of the device, the faster the glass is generated, and the longer the treatment time, the higher the conversion rate into glass.

[0149] Generally, when X-ray diffraction analysis is performed using CuKα rays as a radiation source, when the diffraction peak from the raw material disappears or decreases, it can be judged that the raw material composition of the sulfide-based inorganic solid electrolyte material is vitrified and the desired sulfide-based inorganic solid electrolyte material can be obtained.

[0150] The mechanical treatment in step (B) is preferably performed under an inert gas atmosphere, thereby preventing the sulfide-based inorganic solid electrolyte material from being degraded (eg, oxidized).

[0151] Examples of the inert gas include argon, helium, and nitrogen. To prevent impurities from entering the product, the purity of these inert gases is preferably higher, and to avoid contact with moisture, the dew point is preferably -70°C or lower, more preferably -80°C or lower.

[0152] In step (C), the obtained glassy sulfide-based inorganic solid electrolyte material is heated to crystallize at least a portion thereof, thereby obtaining a glass-ceramic sulfide-based inorganic solid electrolyte material. Here, glass-ceramic refers to a substance in which at least a portion of an inorganic compound is crystallized, and is also called crystallized glass.

[0153] The lower limit of the heat treatment temperature in step (C) is not particularly limited, but is preferably 180° C. or higher, more preferably 200° C. or higher, and even more preferably 220° C. or higher, and the upper limit is preferably less than 450° C., more preferably less than 400° C., and even more preferably less than 350° C. As a result, the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material is further improved.

[0154] The upper limit of the heat treatment temperature in step (C) is not particularly limited, but preferably does not include a step of heating at 450° C. or higher, more preferably does not include a step of heating at 400° C. or higher, and further preferably does not include a step of heating at 350° C. or higher. Thus, the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material is further improved.

[0155] The heat treatment time in step (C) is not particularly limited, but is preferably 0.5 hours to 24 hours, and more preferably 1 hour to 3 hours. This further improves the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material.

[0156] The method of heat treatment in step (C) is not particularly limited, and examples thereof include a method using a heating furnace or a calcining furnace.

[0157] In addition, the heat treatment in step (C) is preferably performed under an inert gas atmosphere, thereby preventing the sulfide-based inorganic solid electrolyte material from being degraded (eg, oxidized).

[0158] In step (D), the obtained sulfide-based inorganic solid electrolyte material in the glass or glass ceramic state is crushed, classified or granulated to obtain a sulfide-based inorganic solid electrolyte material. Step (D) may be performed between step (B) and step (C) or after step (C).

[0159] The pulverization method is not particularly limited, and a known pulverization method such as a mixer, a jet mill, a mortar, a rotary mill, a coffee mill, etc. can be used. In addition, the classification method is also not particularly limited, and a known method such as a sieve can be used.

[0160] From the viewpoint of preventing contact with moisture in the air, the pulverization or classification is preferably performed under an inert gas atmosphere or a vacuum atmosphere.

[0161] In order to obtain the sulfide-based inorganic solid electrolyte material of the present embodiment, it is important to appropriately adjust the above-mentioned steps. However, the method for producing the sulfide-based inorganic solid electrolyte material of the present embodiment is not limited to the above-mentioned method.

[0162] [Sulfide-based inorganic solid electrolyte materials]

[0163] The sulfide-based inorganic solid electrolyte material of the present embodiment is obtained by using the above-mentioned phosphorus sulfide composition of the present embodiment as a raw material.

[0164] The lower limit of the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the present embodiment measured by the method described in the following <Measurement of lithium ion conductivity> is preferably 1.0×10 -3 S / cm or more, more preferably 1.1×10 -3 S / cm or more, more preferably 1.2×10 -3 S / cm or more. Thus, a lithium ion battery having further excellent input-output characteristics can be obtained.

[0165] The upper limit of the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of this embodiment is not particularly limited, and is, for example, 1.0×10 -2 S / cm or less, can be 5.0×10 -3 S / cm or less, can be 3.0×10 -3 S / cm or less, and can also be 2.0×10 -3 S / cm or less.

[0166] <Measurement of lithium ion conductivity>

[0167] First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1 mm.

[0168] Then, the lithium ion conductivity of the obtained disk-shaped sample was measured by an electrochemical device under the conditions of an applied voltage of 10 mV, a measurement frequency range of 0.1 Hz to 3 MHz, and a measurement temperature of 27° C., using a Li foil as an electrode, and an AC impedance method.

[0169] The lithium ion conductivity can be measured using an electrochemical measuring device such as a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Science Instruments.

[0170] The upper limit of the maximum value of the oxidation decomposition current of the sulfide-based inorganic solid electrolyte material of the present embodiment measured by the method described in the following <Measurement of the Maximum Value of the Oxidative Decomposition Current> is preferably 0.5×10 -5 mA or less, preferably 0.2×10 -5 mA or less, more preferably 0.1×10 -5 mA or less, more preferably 0.09×10 -5 mA or less, more preferably 0.08×10 -5Thereby, the oxidative decomposition of the sulfide-based inorganic solid electrolyte material in the lithium ion battery can be further suppressed.

[0171] The lower limit of the maximum value of the oxidation decomposition current of the sulfide-based inorganic solid electrolyte material of the present embodiment is not particularly limited, and is, for example, 0.001×10 -5 mA or more.

[0172] <Determination of the maximum value of the oxidative decomposition current>

[0173] First, 150 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1.3 mm.

[0174] Then, a Li foil as a reference electrode / counter electrode was pressure-bonded to one surface of the obtained disk-shaped sample under the conditions of 18 MPa for 10 minutes, and then a SUS314 foil as a working electrode was attached to the other surface facing upward.

[0175] Then, using an electrochemical device, the maximum value of the oxidative decomposition current of the obtained particles was measured under the conditions of a sweep voltage range of 0 to 10 V, a voltage sweep rate of 5 mV / sec, and a measurement temperature of 25°C.

[0176] The maximum value of the oxidative decomposition current can be measured using an electrochemical measuring device such as a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Science Instruments.

[0177] The sulfide-based inorganic solid electrolyte material of the present embodiment has no peak in the range of 2θ = 27.70 ± 0.50°, a peak in the range of 2θ = 17.90 ± 0.20°, a peak in the range of 2θ = 29.00 ± 0.50°, and a peak in the range of 2θ = 29.75 ± 0.25° in the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the following <X-ray diffraction analysis>.

[0178] <X-ray diffraction analysis>

[0179] Under the conditions of voltage 40 kV, current 40 mA, divergence slit 1°, divergence slit longitudinal limitation 10 mm, scattering slit 1°, light receiving slit 0.3 mm, measurement start angle 3°, and measurement end angle 90°, CuKα rays were used as the ray source to obtain the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material.

[0180] In addition, X-ray diffraction analysis can be performed using an X-ray diffraction apparatus such as RINT2000 manufactured by Rigaku Corporation.

[0181] The X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above-mentioned <X-ray diffraction analysis> is similar to the X-ray diffraction analysis spectrum of α-phase Li3PS4.

[0182] Specifically, the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above <X-ray diffraction analysis> satisfies the following requirements 1 to 3. It should be noted that according to K. Homma, M. Yonemura, M. Nagao, M. Hirayama, R. Kanno, J. Phys. Soc. Jpn., 79, 90-93 (2010), these requirements are also applicable to α-phase Li3PS4.

[0183] Requirement 1: A peak exists within the range of 2θ=17.90±0.20°.

[0184] Requirement 2: A peak exists within the range of 2θ=29.00±0.50°.

[0185] Requirement 3: A peak exists within the range of 2θ=29.75±0.25°.

[0186] As a result of studies, the present inventors have newly found that when the X-ray diffraction analysis spectrum of a sulfide-based inorganic solid electrolyte material has the above-mentioned characteristics, the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material is improved.

[0187] In the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above <X-ray diffraction analysis>, it is preferred that a peak exists in the range of 2θ=20.00±0.20°.

[0188] In the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above <X-ray diffraction analysis>, it is preferred that a peak exists in the range of 2θ=25.90±0.20°.

[0189] In the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above <X-ray diffraction analysis>, it is preferred that the peak existing in the range of 2θ=17.90±0.20° is not divided into two.

[0190] The sulfide-based inorganic solid electrolyte material of the present embodiment preferably contains Li, P, and S as constituent elements.

[0191] The molar ratio of Li to P (Li / P) of the sulfide-based inorganic solid electrolyte material of the present embodiment is preferably 1.0 to 5.0, more preferably 2.0 to 4.0, further preferably 2.5 to 3.8, further preferably 2.8 to 3.6, further preferably 3.0 to 3.5, further preferably 3.1 to 3.4, further preferably 3.1 to 3.3.

[0192] The molar ratio of S to P (S / P) of the sulfide-based inorganic solid electrolyte material of the present embodiment is preferably 2.0 to 6.0, more preferably 3.0 to 5.0, further preferably 3.5 to 4.5, further preferably 3.8 to 4.2, further preferably 3.9 to 4.1.

[0193] Here, the molar ratio of Li to P (Li / P) and the molar ratio of S to P (S / P) can be determined by, for example, ICP emission spectrometry, X-ray analysis, or the like.

[0194] The sulfide-based inorganic solid electrolyte material of the present embodiment preferably contains Li 3 PS 4 .

[0195] The sulfide-based inorganic solid electrolyte material of the present embodiment preferably contains α-type Li 3 PS 4 α-type Li 3 PS 4 can be identified by, for example, X-ray diffraction analysis.

[0196] When the sulfide-based inorganic solid electrolyte material of the present embodiment is in the form of particles, the particle size thereof is not particularly limited. The particle size distribution according to the volume-based particle size distribution of the laser diffraction scattering particle size distribution measurement method is D 50 The lower limit of is preferably 0.1 μm or more, more preferably 0.3 μm or more, and even more preferably 0.5 μm or more. Thus, the handleability of the sulfide-based inorganic solid electrolyte material is further improved.

[0197] In addition, D 50 The upper limit of is preferably 150 μm or less, more preferably 120 μm or less, and still more preferably 100 μm or less. This further improves the lithium ion conductivity.

[0198] The sulfide-based inorganic solid electrolyte material of the present embodiment can be used for any application requiring lithium ion conductivity, and can be preferably used for lithium ion batteries, particularly all-solid-state lithium ion batteries.

[0199] [Sulfide-based inorganic solid electrolyte]

[0200] The sulfide-based inorganic solid electrolyte of the present embodiment includes the sulfide-based inorganic solid electrolyte material of the present embodiment described above.

[0201] The sulfide-based inorganic solid electrolyte of the present embodiment may include, as a component other than the sulfide-based inorganic solid electrolyte material of the present embodiment described above, for example, a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment described above, within a range not impairing the purpose of the present invention.

[0202] As solid electrolyte materials different from the sulfide-based inorganic solid electrolyte materials of the present embodiment described above, for example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials that are different from the sulfide-based inorganic solid electrolyte materials of the present embodiment described above; organic solid electrolyte materials such as polymer electrolytes; and the like can be cited.

[0203] As sulfide-based inorganic solid electrolyte materials of a different type from the sulfide-based inorganic solid electrolyte materials of the present embodiment described above, for example, Li2S-P2S5 materials, Li2S-SiS2 materials, Li2S-GeS2 materials, Li2S-Al2S3 materials, Li2S-SiS2-Li3PO4 materials, Li2S-P2S5-GeS2 materials, Li2S-Li2O-P2S5-SiS2 materials, Li2S-GeS2-P2S5-SiS2 materials, Li2S-SnS2-P2S5-SiS2 materials, Li2S-P2S5-Li3N materials, Li2S2+X-P4S3 materials, Li2S-P2S5-P4S3 materials, etc. can be cited.

[0204] Here, for example, the Li2S-P2S5 material refers to a solid electrolyte material obtained by chemically reacting an inorganic composition containing at least Li2S (lithium sulfide) and P2S5 with each other through mechanical treatment.

[0205] Here, lithium sulfide also includes lithium polysulfide.

[0206] As the above-mentioned oxide-based inorganic solid electrolyte material, for example, sodium superion conductor type materials (NASICON type materials) such as LiTi2(PO4)3, LiZr2(PO4)3, and LiGe2(PO4)3 can be cited; (La 0.5+x Li 0.5-3x )TiO3 and other perovskite materials; Li2O-P2O5 materials; Li2O-P2O5-Li3N materials; etc.

[0207] As other lithium-based inorganic solid electrolyte materials, for example, LiPON, LiNbO3, LiTaO3, Li3PO4, LiPO 4-x Nx (x is 0<x≤1), LiN, LiI, LISICON, etc.

[0208] Furthermore, glass ceramics obtained by precipitating crystals of the above-mentioned inorganic solid electrolyte can also be used as an inorganic solid electrolyte material.

[0209] Examples of the organic solid electrolyte material include polymer electrolytes such as dry polymer electrolytes and gel electrolytes.

[0210] [Sulfide-based inorganic solid electrolyte membrane]

[0211] The sulfide-based inorganic solid electrolyte membrane of the present embodiment contains the above-described solid electrolyte of the present embodiment as a main component.

[0212] The sulfide-based inorganic solid electrolyte membrane of the present embodiment is used, for example, to constitute a solid electrolyte layer of an all-solid-state lithium-ion battery. As an example of an all-solid-state lithium-ion battery to which the solid electrolyte membrane of the present embodiment is applied, there can be cited a battery in which a positive electrode, a solid electrolyte layer, and a negative electrode are stacked in sequence. In this case, the solid electrolyte layer is composed of a solid electrolyte membrane.

[0213] The average thickness of the sulfide-based inorganic solid electrolyte membrane of this embodiment is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. This can further suppress the loss of solid electrolyte and the occurrence of cracks on the surface of the solid electrolyte membrane.

[0214] The average thickness of the sulfide-based inorganic solid electrolyte membrane of this embodiment is preferably 500 μm or less, more preferably 200 μm or less, and even more preferably 100 μm or less. This can further reduce the impedance of the solid electrolyte membrane, and as a result, the battery characteristics of the obtained all-solid-state lithium-ion battery are further improved.

[0215] The sulfide-based inorganic solid electrolyte membrane of the present embodiment is preferably a pressurized body of a particulate solid electrolyte. That is, it is preferred that the particulate solid electrolyte is pressurized to form a solid electrolyte membrane having a predetermined strength due to the anchoring effect between the solid electrolyte materials. This can further suppress the loss of the solid electrolyte and the generation of cracks on the surface of the solid electrolyte membrane.

[0216] The lower limit of the content of the above-mentioned sulfide-based inorganic solid electrolyte material of the present embodiment in the sulfide-based inorganic solid electrolyte membrane of the present embodiment is preferably 50 mass % or more, more preferably 60 mass % or more, further preferably 70 mass % or more, further preferably 80 mass % or more, further preferably 90 mass % or more.

[0217] Thus, the contact between solid electrolytes can be improved and the interface contact resistance of the solid electrolyte membrane can be reduced, resulting in further improvement of the lithium ion conductivity of the solid electrolyte membrane. Moreover, by using such a solid electrolyte membrane with improved lithium ion conductivity, the battery characteristics of the all-solid-state lithium ion battery can be further improved.

[0218] The upper limit of the content of the above-mentioned sulfide-based inorganic solid electrolyte material of the present embodiment in the sulfide-based inorganic solid electrolyte membrane of the present embodiment is not particularly limited, and is, for example, 100 mass % or less.

[0219] The planar shape of the sulfide-based inorganic solid electrolyte membrane of the present embodiment is not particularly limited and can be appropriately selected according to the shapes of the electrodes and the current collector, and can be, for example, a rectangular shape.

[0220] The sulfide-based inorganic solid electrolyte membrane of the present embodiment may contain a binder resin, and the content of the binder resin is preferably less than 0.5% by mass, more preferably 0.1% by mass or less, further preferably 0.05% by mass or less, and further preferably 0.01% by mass or less. In addition, it is more preferred that the solid electrolyte membrane of the present embodiment does not substantially contain a binder resin.

[0221] Thus, the contact between solid electrolytes can be improved and the interface contact resistance of the solid electrolyte membrane can be reduced, resulting in further improvement of the lithium ion conductivity of the solid electrolyte membrane. Moreover, by using such a solid electrolyte membrane with improved lithium ion conductivity, the battery characteristics of the all-solid-state lithium ion battery can be further improved.

[0222] It should be noted that “substantially free of binder resin” means that the binder resin may be contained to the extent that the effect of the present embodiment is not impaired. In addition, when an adhesive resin layer is provided between the solid electrolyte layer and the positive electrode or the negative electrode, the adhesive resin from the adhesive resin layer present near the interface between the solid electrolyte layer and the adhesive resin layer is excluded from the “binder resin in the solid electrolyte membrane”.

[0223] The binder resin is a binder generally used in lithium ion batteries for bonding inorganic solid electrolyte materials, and examples thereof include polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, and polyimide.

[0224] For example, the sulfide-based inorganic solid electrolyte membrane of the present embodiment can be obtained by depositing a particulate solid electrolyte in a film shape on the cavity surface of a mold or on the surface of a substrate and then pressurizing the deposited solid electrolyte in a film shape.

[0225] There is no particular limitation on the method of pressurizing the above-mentioned solid electrolyte. For example, when the particulate solid electrolyte is deposited on the cavity surface of the mold, pressurization using the mold and the die can be used; when the particulate solid electrolyte is deposited on the surface of the substrate, pressurization using the mold and the die, roller pressing, flat plate pressing, etc. can be used.

[0226] The pressure at which the solid electrolyte is pressurized is, for example, 10 MPa to 500 MPa.

[0227] In addition, as required, the inorganic solid electrolyte deposited in a film form may be pressurized and heated at the same time. As long as the heating and pressurization are performed, the fusion and bonding between the solid electrolytes will be caused, and the strength of the obtained solid electrolyte membrane will be further improved, and as a result, the loss of solid electrolyte and the generation of cracks on the surface of the solid electrolyte membrane can be further suppressed.

[0228] The temperature for heating the solid electrolyte is, for example, 40° C. or higher and 500° C. or lower.

[0229] [Lithium-ion battery]

[0230] The lithium ion battery of the present embodiment is a lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, and at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material of the present embodiment described above.

[0231] Figure 1 It is a cross-sectional view showing an example of the structure of the lithium ion battery according to the present embodiment.

[0232] The lithium ion battery 100 of the present embodiment includes, for example, a positive electrode 110 including a positive electrode active material layer 101 , an electrolyte layer 120 , and a negative electrode 130 including a negative electrode active material layer 103 .

[0233] Furthermore, at least one of the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 contains the above-mentioned sulfide-based inorganic solid electrolyte material of the present embodiment. In addition, it is preferred that all of the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 contain the above-mentioned sulfide-based inorganic solid electrolyte material of the present embodiment.

[0234] It should be noted that, in this embodiment, unless otherwise specified, the layer containing the positive electrode active material is referred to as the positive electrode active material layer 101. As required, the positive electrode 110 may include a current collector 105 in addition to the positive electrode active material layer 101, or may not include the current collector 105. In addition, in this embodiment, unless otherwise specified, the layer containing the negative electrode active material is referred to as the negative electrode active material layer 103. As required, the negative electrode 130 may include a current collector 105 in addition to the negative electrode active material layer 103, or may not include the current collector 105.

[0235] The shape of the lithium ion battery 100 of the present embodiment is not particularly limited, and may be any other shape such as a cylinder, a coin, a rectangle, and a film.

[0236] The lithium ion battery 100 of this embodiment is manufactured by a commonly known method, for example, by stacking the positive electrode 110, the electrolyte layer 120, and the negative electrode 130 to form a cylindrical, coin-shaped, rectangular, film-shaped, or other arbitrary shape, and sealing a non-aqueous electrolyte as needed.

[0237] <Positive electrode>

[0238] The positive electrode 110 is not particularly limited, and a positive electrode commonly used in lithium ion batteries can be used. The positive electrode 110 is not particularly limited, and can be manufactured according to a generally known method. For example, it can be obtained by forming a positive electrode active material layer 101 containing a positive electrode active material on the surface of a current collector 105 such as an aluminum foil.

[0239] The thickness and density of the positive electrode active material layer 101 are appropriately determined according to the intended use of the battery, and therefore are not particularly limited and can be set according to generally known information.

[0240] The positive electrode active material layer 101 contains a positive electrode active material.

[0241] There are no particular limitations on the positive electrode active material, and commonly known positive electrode active materials can be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium-manganese-nickel oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3O2), olivine-type lithium phosphorus oxide (LiFePO4) and other composite oxides; conductive polymers such as polyaniline and polypyrrole; sulfide-based positive electrode active materials such as Li2S, CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, Li-Mo-S compounds, Li-Ti-S compounds, Li-VS compounds, and Li-Fe-S compounds; materials with sulfur as the active material, such as sulfur-impregnated acetylene black, sulfur-impregnated porous carbon, and mixed powder of sulfur and carbon; etc.

[0242] Among them, from the viewpoint of having a higher discharge capacity density and better cycle characteristics, a sulfide-based positive electrode active material is preferred, and one or more selected from a Li-Mo-S compound, a Li-Ti-S compound, and a Li-VS compound is more preferred.

[0243] Here, the Li—Mo—S compound is a compound containing Li, Mo, and S as constituent elements, and can be generally obtained by chemically reacting an inorganic composition containing molybdenum sulfide and lithium sulfide as raw materials by mechanical treatment.

[0244] The Li—Ti—S compound is a compound containing Li, Ti, and S as constituent elements, and can be generally obtained by chemically reacting an inorganic composition containing titanium sulfide and lithium sulfide as raw materials by mechanical treatment.

[0245] The Li—VS compound is a compound containing Li, V, and S as constituent elements, and can be generally obtained by chemically reacting an inorganic composition containing vanadium sulfide and lithium sulfide as raw materials by mechanical treatment.

[0246] The positive electrode active material layer 101 is not particularly limited, and may include, as components other than the above-mentioned positive electrode active material, one or more materials selected from a binder resin, a thickener, a conductive aid, a solid electrolyte material, etc. Each material is described below.

[0247] The positive electrode active material layer 101 may contain a binder resin having a function of binding the positive electrode active materials to each other and binding the positive electrode active material to the current collector 105 .

[0248] The binder resin of the present embodiment is not particularly limited as long as it is a common binder resin that can be used for lithium ion batteries, and examples thereof include polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, and polyimide.

[0249] From the viewpoint of ensuring the fluidity of the slurry suitable for coating, the positive electrode active material layer 101 may also include a thickener. As a thickener, there is no particular limitation as long as it is a common thickener that can be used in lithium ion batteries. For example, cellulose polymers such as carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose and their ammonium salts and alkali metal salts, polycarboxylic acids, polyethylene oxide, polyvinyl pyrrolidone, polyacrylates, polyvinyl alcohol and other water-soluble polymers can be cited.

[0250] The positive electrode active material layer 101 may contain a conductive aid from the viewpoint of improving the conductivity of the positive electrode 110. The conductive aid is not particularly limited as long as it is a common conductive aid that can be used in lithium ion batteries, and examples thereof include carbon black such as acetylene black and Ketjen black; and carbon materials such as vapor-grown carbon fibers.

[0251] The positive electrode of the lithium ion battery of the present embodiment may contain a solid electrolyte including the sulfide-based inorganic solid electrolyte material of the present embodiment described above, or may contain a solid electrolyte including a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment described above.

[0252] As a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment described above, there is no particular limitation as long as it has ion conductivity and insulation, and solid electrolyte materials commonly used in lithium-ion batteries can be used. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials that are different from the sulfide-based inorganic solid electrolyte material of the present embodiment described above can be cited; organic solid electrolyte materials such as polymer electrolytes. More specifically, the inorganic solid electrolyte materials cited in the description of the solid electrolyte of the present embodiment described above can be used.

[0253] The mixing ratio of various materials in the positive electrode active material layer 101 is appropriately determined according to the intended use of the battery, and therefore is not particularly limited and can be set according to generally known information.

[0254] <Negative electrode>

[0255] The negative electrode 130 is not particularly limited, and materials commonly used in lithium-ion batteries can be used. The negative electrode 130 is not particularly limited, and can be manufactured according to a generally known method. For example, it can be obtained by forming a negative electrode active material layer 103 containing a negative electrode active material on the surface of a current collector 105 such as copper.

[0256] The thickness and density of the negative electrode active material layer 103 are appropriately determined according to the intended use of the battery, and therefore are not particularly limited and can be set according to generally known information.

[0257] The negative electrode active material layer 103 contains a negative electrode active material.

[0258] The negative electrode active material is not particularly limited as long as it is a common negative electrode active material that can be used for the negative electrode of a lithium ion battery. For example, carbonaceous materials such as natural graphite, artificial graphite, resin carbon, carbon fiber, activated carbon, hard carbon, and soft carbon can be cited; metal materials based on lithium, lithium alloys, tin, tin alloys, silicon, silicon alloys, gallium, gallium alloys, indium, indium alloys, aluminum, and aluminum alloys; conductive polymers such as polyacene, polyacetylene, and polypyrrole; lithium titanium composite oxides (such as Li4Ti5O 12 )wait.

[0259] The negative electrode active material layer 103 is not particularly limited, and as a component other than the above-mentioned negative electrode active material, for example, it may also contain one or more materials selected from a binder resin, a thickener, a conductive aid, a solid electrolyte material, etc. These materials are not particularly limited, and for example, the same materials as those used in the above-mentioned positive electrode 110 can be cited.

[0260] Since the mixing ratio of each material in the negative electrode active material layer 103 is appropriately determined according to the use of the battery, etc., it is not particularly limited and can be set according to generally known information.

[0261] The negative electrode of the lithium ion battery of the present embodiment may include a solid electrolyte containing the sulfide-based inorganic solid electrolyte material of the present embodiment described above, or may include a solid electrolyte containing a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment described above.

[0262] As a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment described above, there is no particular limitation as long as it has ion conductivity and insulation, and materials commonly used in lithium-ion batteries can be used. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials that are different from the sulfide-based inorganic solid electrolyte material of the present embodiment described above can be cited; organic solid electrolyte materials such as polymer electrolytes. More specifically, the inorganic solid electrolyte materials cited in the description of the solid electrolyte of the present embodiment described above can be used.

[0263] <Electrolyte layer>

[0264] Next, the electrolyte layer 120 will be described. The electrolyte layer 120 is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103 .

[0265] Examples of the electrolyte layer 120 include a layer in which a separator is impregnated with a non-aqueous electrolyte solution and a solid electrolyte layer containing a solid electrolyte.

[0266] The separator of this embodiment is not particularly limited as long as it can electrically insulate the positive electrode 110 and the negative electrode 130 and has a function of allowing lithium ions to pass therethrough. For example, a porous film can be used.

[0267] As the porous film, a microporous polymer film is preferably used, and examples of the material include polyolefin, polyimide, polyvinylidene fluoride, polyester, etc. In particular, a porous polyolefin film is preferred, and specific examples include a porous polyethylene film, a porous polypropylene film, and the like.

[0268] The non-aqueous electrolyte solution is obtained by dissolving an electrolyte in a solvent.

[0269] As the electrolyte, any known lithium salt can be used, and it can be selected according to the type of active material. For example, LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, lower fatty acid carboxylic acid lithium, etc.

[0270] The solvent for dissolving the above-mentioned electrolyte is not particularly limited as long as it is a solvent commonly used as a liquid for dissolving the electrolyte, and examples thereof include carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), and vinylene carbonate (VC); lactones such as γ-butyrolactone and γ-valerolactone; ethers such as trimethoxymethane, 1,2-dimethoxyethane, diethyl ether, 2-ethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran; and sulfoxides such as dimethyl sulfoxide. oxolanes such as 1,3-dioxolane and 4-methyl-1,3-dioxolane; nitrogen-containing compounds such as acetonitrile, nitromethane, formamide and dimethylformamide; organic acid esters such as methyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate and ethyl propionate; triesters of phosphate and diethylene glycol dimethyl ether (diglyme); triethylene glycol dimethyl ether (triglyme); sulfolanes such as sulfolane and methyl sulfolane; oxazolidinones such as 3-methyl-2-oxazolidinone; sultones such as 1,3-propane sultone, 1,4-butane sultone and naphthalene sultone; etc.

[0271] The solid electrolyte layer of the lithium ion battery of the present embodiment is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103 , and is a layer formed of a solid electrolyte containing a solid electrolyte material.

[0272] The content of the solid electrolyte contained in the solid electrolyte layer of the lithium ion battery of the present embodiment is not particularly limited as long as it is a ratio that can obtain the desired insulation properties, but is preferably 10% by volume or more and 100% by volume or less, preferably 50% by volume or more and 100% by volume or less, preferably 70% by volume or more and 100% by volume or less, preferably 90% by volume or more and 100% by volume or less, and more preferably contains substantially no components other than the solid electrolyte.

[0273] It should be noted that “substantially containing no components other than the solid electrolyte” means that components other than the solid electrolyte may be contained to the extent that the effects of the present embodiment are not impaired.

[0274] The solid electrolyte contained in the solid electrolyte layer of the lithium ion battery of the present embodiment is not particularly limited as long as it has lithium ion conductivity, but is preferably the solid electrolyte of the present embodiment described above.

[0275] The content of the solid electrolyte of the present embodiment contained in the solid electrolyte layer of the lithium-ion battery of the present embodiment is not particularly limited as long as it is a ratio that can obtain the desired insulation properties, and is preferably greater than 10 volume % and less than 100 volume %, more preferably greater than 50 volume % and less than 100 volume %, further preferably greater than 70 volume % and less than 100 volume %, further preferably greater than 90 volume % and less than 100 volume %, and it is particularly preferred that it does not substantially contain any components other than the solid electrolyte of the present embodiment mentioned above.

[0276] It should be noted that “substantially containing no components other than the solid electrolyte of the present embodiment described above” means that components other than the solid electrolyte of the present embodiment described above may be contained to the extent that the effects of the present embodiment are not impaired.

[0277] The solid electrolyte layer of the lithium ion battery of this embodiment may also contain a binder resin. By containing a binder resin, a flexible solid electrolyte layer can be obtained. As the binder resin, for example, fluorine-containing binders such as polytetrafluoroethylene and polyvinylidene fluoride can be cited.

[0278] The thickness of the solid electrolyte layer of the lithium ion battery of the present embodiment is preferably 0.1 μm or more and 1000 μm or less, and more preferably 0.1 μm or more and 300 μm or less.

[0279] [Method for producing a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material]

[0280] The method for producing a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material according to the present embodiment includes a step of sorting a phosphorus sulfide composition having a reactivity of 5.0° C. / min or more measured by the following [Method 1].

[0281] The lower limit of the reactivity is preferably 6.0°C / min or more, more preferably 6.5°C / min or more, further preferably 6.8°C / min or more, further preferably 7.0°C / min or more, further preferably 7.5°C / min or more, further preferably 8.0°C / min or more. The upper limit of the reactivity is not particularly limited, for example, 30.0°C / min or less, 15.0°C / min or less, 10.0°C / min or less, or 9.0°C / min or less.

[0282] [Method 1]

[0283] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0284] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0285] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0286] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0287] The reactivity is derived from the following formula (1).

[0288] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0289] [Quality Management Method for Phosphorus Sulfide Composition for Sulfide-Based Inorganic Solid Electrolyte Material]

[0290] The quality control method of the phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material according to the present embodiment includes the step of judging as acceptable a phosphorus sulfide composition having a reactivity of 5.0° C. / min or more as measured by the following [Method 1].

[0291] The lower limit of the reactivity is preferably 6.0°C / min or more, more preferably 6.5°C / min or more, further preferably 6.8°C / min or more, further preferably 7.0°C / min or more, further preferably 7.5°C / min or more, further preferably 8.0°C / min or more. The upper limit of the reactivity is not particularly limited, for example, 30.0°C / min or less, 15.0°C / min or less, 10.0°C / min or less, or 9.0°C / min or less.

[0292] [Method 1]

[0293] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0294] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0295] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0296] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0297] The reactivity is derived from the following formula (1).

[0298] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0299] 2. Second Implementation

[0300] Hereinafter, a second embodiment of the present invention will be described.

[0301] [Sulfide-based inorganic solid electrolyte materials]

[0302] The sulfide-based inorganic solid electrolyte material of the present embodiment is a sulfide-based inorganic solid electrolyte material containing Li, P and S as constituent elements. In the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the following <X-ray diffraction analysis>, there is no peak in the range of 2θ = 27.70 ± 0.50 °, there is a peak in the range of 2θ = 17.90 ± 0.20 °, there is a peak in the range of 2θ = 29.00 ± 0.50 °, and there is a peak in the range of 2θ = 29.75 ± 0.25 °.

[0303] <X-ray diffraction analysis>

[0304] An X-ray diffraction apparatus (RINT2000 manufactured by Rigaku Corporation) was used with a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a divergence slit longitudinal limit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, and a measurement end angle of 90°. CuKα rays were used as the ray source. In addition, a glass sample plate (product number 9200, sample portion 20 mm×20 mm, depth 0.5 mm) was used as a sample holder to obtain an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material.

[0305] The X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above-mentioned <X-ray diffraction analysis> is similar to the X-ray diffraction analysis spectrum of α-phase Li3PS4.

[0306] Specifically, the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above <X-ray diffraction analysis> satisfies the following requirements 1 to 3. It should be noted that according to K. Homma, M. Yonemura, M. Nagao, M. Hirayama, R. Kanno, J. Phys. Soc. Jpn., 79, 90-93 (2010), these requirements are also applicable to α-phase Li3PS4.

[0307] Requirement 1: A peak exists within the range of 2θ=17.90±0.20°.

[0308] Requirement 2: A peak exists within the range of 2θ=29.00±0.50°.

[0309] Requirement 3: A peak exists within the range of 2θ=29.75±0.25°.

[0310] As a result of studies, the present inventors have newly found that when the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material has the above-mentioned characteristics, the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material is improved.

[0311] It is preferable that, in the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above <X-ray diffraction analysis>, a peak exists in the range of 2θ=20.00±0.20°.

[0312] It is preferable that, in the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above <X-ray diffraction analysis>, a peak exists in the range of 2θ=25.90±0.20°.

[0313] Preferably, in the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material of the present embodiment obtained by the method described in the above <X-ray diffraction analysis>, the peak existing in the range of 2θ=17.90±0.20° is not divided into two.

[0314] In the sulfide-based inorganic solid electrolyte material of the present embodiment, the molar ratio of Li to P (Li / P) of the sulfide-based inorganic solid electrolyte material is preferably 1.0 to 5.0, more preferably 2.0 to 4.0, further preferably 2.5 to 3.5, further preferably 2.7 to 3.3, further preferably 2.8 to 3.2, further preferably 2.9 to 3.1.

[0315] In the sulfide-based inorganic solid electrolyte material of the present embodiment, the molar ratio of S to P (S / P) of the sulfide-based inorganic solid electrolyte material is preferably 2.0 to 6.0, more preferably 3.0 to 5.0, further preferably 3.5 to 4.5, further preferably 3.8 to 4.2, further preferably 3.9 to 4.1.

[0316] Here, the molar ratio of Li to P (Li / P) and the molar ratio of S to P (S / P) can be determined by, for example, ICP emission spectrometry, X-ray analysis, or the like.

[0317] The sulfide-based inorganic solid electrolyte material of the present embodiment preferably contains Li 3 PS 4 .

[0318] The content of Li3PS4 in the sulfide-based inorganic solid electrolyte material of the present embodiment is preferably 95% by mass or more, more preferably 97% by mass or more, and further preferably 99% by mass or more.

[0319] When the sulfide-based inorganic solid electrolyte material of the present embodiment is in the form of particles, D in the volume-based particle size distribution according to the laser diffraction scattering particle size distribution measurement method is 50 The lower limit of is preferably 0.1 μm or more, more preferably 0.3 μm or more, and even more preferably 0.5 μm or more. Thus, the handleability of the sulfide-based inorganic solid electrolyte material is further improved.

[0320] In addition, D 50 The upper limit of is preferably 150 μm or less, more preferably 120 μm or less, and still more preferably 100 μm or less. This further improves the lithium ion conductivity.

[0321] The lower limit of the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the present embodiment measured by the method described in the following <Measurement of lithium ion conductivity> is preferably 1.0×10 -3 S / cm or more, more preferably 1.1×10 -3 S / cm or more, more preferably 1.2×10 -3 S / cm or more. Thus, a lithium ion battery having further excellent input-output characteristics can be obtained.

[0322] The upper limit of the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of this embodiment is not particularly limited, and is, for example, 1.0×10 -2 S / cm or less, can be 5.0×10 -3 S / cm or less, can be 3.0×10 -3 S / cm or less, and can also be 2.0×10 -3 S / cm or less.

[0323] <Measurement of lithium ion conductivity>

[0324] First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1 mm.

[0325] The lithium ion conductivity of the obtained disk-shaped sample was then measured by an AC impedance method using a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Science Instruments under conditions of an applied voltage of 10 mV, a measurement frequency range of 0.1 Hz to 3 MHz, and a measurement temperature of 27° C. using a Li foil as an electrode.

[0326] The upper limit of the maximum value of the oxidation decomposition current of the sulfide-based inorganic solid electrolyte material of the present embodiment measured by the method described in the following <Measurement of the Maximum Value of the Oxidative Decomposition Current> is preferably 0.5×10-5 mA or less, preferably 0.2×10 -5 mA or less, more preferably 0.1×10 -5 mA or less, more preferably 0.09×10 -5 mA or less, more preferably 0.08×10 -5 Thereby, the oxidative decomposition of the sulfide-based inorganic solid electrolyte material in the lithium ion battery can be further suppressed.

[0327] The lower limit of the maximum value of the oxidation decomposition current of the sulfide-based inorganic solid electrolyte material of the present embodiment is not particularly limited, and is, for example, 0.001×10 -5 mA or more.

[0328] <Determination of the maximum value of the oxidative decomposition current>

[0329] First, 150 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1.3 mm.

[0330] Then, a Li foil as a reference electrode / counter electrode was pressure-bonded to one surface of the obtained disk-shaped sample under the conditions of 18 MPa for 10 minutes, and then a SUS314 foil as a working electrode was attached to the other surface facing upward.

[0331] Then, using a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Science Instruments, the maximum value of the oxidative decomposition current of the obtained particles was measured under the conditions of a sweep voltage range of 0 to 10 V, a voltage sweep rate of 5 mV / sec, and a measurement temperature of 25°C.

[0332] [Method for producing sulfide-based inorganic solid electrolyte material]

[0333] The method for producing the sulfide-based inorganic solid electrolyte material of the present embodiment is the same as the method for producing the sulfide-based inorganic solid electrolyte material of the first embodiment, and therefore description thereof is omitted here.

[0334] [Sulfide-based inorganic solid electrolyte]

[0335] The sulfide-based inorganic solid electrolyte of the present embodiment is the same as the sulfide-based inorganic solid electrolyte material of the first embodiment except that it includes the sulfide-based inorganic solid electrolyte material of the present embodiment described above, and therefore, the description thereof is omitted here.

[0336] [Sulfide-based inorganic solid electrolyte membrane]

[0337] The sulfide-based inorganic solid electrolyte membrane of the present embodiment is the same as the sulfide-based inorganic solid electrolyte membrane of the first embodiment except that it contains the above-described solid electrolyte of the present embodiment as a main component, and therefore the description thereof is omitted here.

[0338] [Lithium-ion battery]

[0339] The lithium ion battery of this embodiment is the same as the lithium ion battery of the first embodiment except that at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material of this embodiment, so the description is omitted here.

[0340] As mentioned above, although embodiment of this invention was described, these are an example of this invention, and various structures other than the above-mentioned can also be adopted.

[0341] It should be noted that the present invention is not limited to the above-described embodiments, and modifications, improvements, etc. within the scope that can achieve the object of the present invention are also included in the present invention.

[0342] Example

[0343] Hereinafter, the present invention will be described by way of Examples and Comparative Examples, but the present invention is not limited thereto.

[0344] [Preparation of sulfide-based inorganic solid electrolyte materials]

[0345] <Example 1>

[0346] First, in an argon environment at 20°C, a total of 2.1 g of powdered P2S5 (product name: Normal / S, batch number 22D1218594, hereinafter referred to as "phosphorus sulfide composition 1") and Li2S (manufactured by Furukawa Metals Co., Ltd., purity 99.9%) were weighed. At this time, the molar ratio was set to Li2S:P2S5=3:1. That is, the molar ratio of the elements was Li:P=3:1, S:P=4:1, Li / P=3, S / P=4.

[0347] Step (a): Under an argon atmosphere at 20° C., the weighed phosphorus sulfide composition 1 and Li 2 S were ground and mixed in a mortar to obtain a mixture (a).

[0348] Step (b): 2.1 g of the mixture (a) obtained in step (a) was subjected to mechanochemical treatment in an argon environment at 20° C. using a planetary ball mill (45 mL zirconia container, using 18 zirconia balls with a diameter of 10 mm) to obtain material (1). Specifically, mechanical grinding was performed at 400 rpm for 10 minutes, followed by standing for 5 minutes, and the treatment was repeated 120 times to obtain material (b). In step (b), powder adhering to the wall surface of the zirconia container and the surface of the zirconia balls was scraped off at 15 hours from the start of the mechanochemical treatment.

[0349] Step (c): The material (b) obtained in step (b) is placed in a carbon crucible, and heat-treated at 270°C for 2 hours in a heating furnace under an argon environment to obtain a sulfide-based inorganic solid electrolyte material 1 containing Li3PS4.

[0350] <Example 2>

[0351] A sulfide-based inorganic solid electrolyte material 2 containing Li3PS4 was obtained in the same manner as in Example 1, except that powdered P2S5 (product name: Normal / S, batch number 22D1218453, hereinafter referred to as "phosphorus sulfide composition 2") was used instead of phosphorus sulfide composition 1.

[0352] <Comparative Example 1>

[0353] Sulfide-based inorganic solid electrolyte material 3 was obtained in the same manner as in Example 1 except that powdered P2S5 (product name: Normal / S, lot number 22D1221141, hereinafter referred to as “phosphorus sulfide composition 3”) was used instead of phosphorus sulfide composition 1.

[0354] <Comparative Example 2>

[0355] First, powdered P2S5 (product name: Normal / S, batch number 22D1221141) was placed in a quartz container and placed in a vacuum heating device (manufactured by Furukawa Machinery & Metals Co., Ltd.). Under reduced pressure conditions of -0.094 MPa, the temperature was raised from 30°C to 350°C in 15 minutes, and then heated at 350°C for 10 minutes.

[0356] Then, the quartz container heated to 350° C. was immersed in a bucket filled with water while the valves of each part were closed and the vacuum state was maintained, and was rapidly cooled to 30° C. The time required to cool from 350° C. to 30° C. was 3 minutes. The component accumulated at the bottom of the quartz container cooled to 30° C. was referred to as “phosphorus sulfide composition 4”.

[0357] Then, a sulfide-based inorganic solid electrolyte material 4 was obtained in the same manner as in Example 1 except that the phosphorus sulfide composition 4 was used instead of the phosphorus sulfide composition 1.

[0358] [Measurement method of reactivity]

[0359] The reactivity of phosphorus sulfide compositions 1 to 4 was measured by the following method. The results are shown in Table 1.

[0360] First, P2S5 was crushed in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and the oversize fraction of 10 g or more was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0361] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0362] The time when the entire amount of the test powder was added was defined as the measurement start time T0, and the temperature of the liquid in the tall beaker was measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 was defined as the measurement start temperature Tm0.

[0363] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max The temperature of the liquid in the tall beaker measured at Tmax is set as the maximum temperature Tm max .

[0364] The reactivity is derived from the following formula (1).

[0365] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0366] [Measurement of lithium ion conductivity]

[0367] The lithium ion conductivity of the sulfide-based inorganic solid electrolyte materials 1 to 4 was measured by the following method. The results are shown in Table 1.

[0368] First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1 mm.

[0369] Then, the lithium ion conductivity of the obtained disk-shaped sample was measured by an AC impedance method using a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Science Instruments under the conditions of an applied voltage of 10 mV, a measurement frequency range of 0.1 Hz to 3 MHz, and a measurement temperature of 27°C, using Li foil as an electrode.

[0370] [Measurement of Maximum Oxidative Decomposition Current]

[0371] The maximum values ​​of the oxidation decomposition currents of the sulfide-based inorganic solid electrolyte materials 1 to 4 were measured by the following method.

[0372] First, 150 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1.3 mm.

[0373] Then, a Li foil as a reference electrode / counter electrode was pressure-bonded to one surface of the obtained disk-shaped sample under the conditions of 18 MPa for 10 minutes, and then a SUS314 foil as a working electrode was attached to the other surface facing upward.

[0374] Then, using a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Science Instruments, the maximum value of the oxidative decomposition current of the obtained particles was measured under the conditions of a sweep voltage range of 0 to 10 V, a voltage sweep rate of 5 mV / sec, and a measurement temperature of 25°C.

[0375] Table 1

[0376]

[0377] The sulfide-based inorganic solid electrolyte material of the example exhibited higher lithium ion conductivity than the comparative example. This shows that the phosphorus sulfide composition of the present embodiment can produce a sulfide-based inorganic solid electrolyte material having improved lithium ion conductivity.

[0378] [X-ray diffraction analysis]

[0379] An X-ray diffraction apparatus (RINT2000, manufactured by Rigaku Corporation) was used with a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a divergence slit longitudinal limit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, and a measurement end angle of 90°. CuKα rays were used as the ray source. In addition, a glass sample plate (product number 9200, sample portion 20 mm×20 mm, depth 0.5 mm) was used as a sample holder to obtain X-ray diffraction analysis spectra of sulfide-based inorganic solid electrolyte materials 1 to 4.

[0380] Figure 2 The X-ray diffraction analysis spectra of the sulfide-based inorganic solid electrolyte materials 1 to 4 are shown. Figure 3 An enlarged view of the range of 2θ=10 to 35° of the X-ray diffraction analysis spectra of the sulfide-based inorganic solid electrolyte materials 1 to 4 is shown.

[0381] In the X-ray diffraction analysis spectra of the sulfide-based inorganic solid electrolyte materials of Examples 1 and 2, there is no peak in the range of 2θ=27.70±0.50°, there is a peak in the range of 2θ=17.90±0.20°, there is a peak in the range of 2θ=29.00±0.50°, and there is a peak in the range of 2θ=29.75±0.25°.

[0382] On the other hand, in the X-ray diffraction analysis spectra of the sulfide-based inorganic solid electrolyte materials of Comparative Examples 1 and 2, a peak exists in the range of 2θ=27.70±0.50°.

[0383] In the X-ray diffraction analysis spectra of the sulfide-based inorganic solid electrolyte materials of Examples 1 and 2, the peak present in the range of 2θ=17.90±0.20 was not divided into two.

[0384] On the other hand, in the X-ray diffraction analysis spectra of the sulfide-based inorganic solid electrolyte materials of Comparative Examples 1 and 2, the peak present in the range of 2θ=17.90±0.20 is divided into two.

[0385] This application is based on Japanese patent application No. 2022-128495, Japanese patent application No. 2022-128496 and Japanese patent application No. 2022-128497 filed on August 10, 2022, and claims the priority of these Japanese patent applications, the entire contents of which are incorporated herein by reference in this application.

[0386] The present invention can also be implemented in the following manners.

[0387] [1a] A phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, wherein the phosphorus sulfide composition has a reactivity of 5.0°C / min or more as measured by the following [Method 1].

[0388] [Method 1]

[0389] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0390] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0391] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0392] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0393] The reactivity is derived from the following formula (1).

[0394] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0395] [2a] The phosphorus sulfide composition according to [1a] above, wherein the phosphorus sulfide composition contains P2S5.

[0396] [3a] The phosphorus sulfide composition according to [2a] above, wherein the content of the P2S5 in the phosphorus sulfide composition is 95% by mass or more.

[0397] [4a] The phosphorus sulfide composition according to any one of [1a] to [3a] above, wherein the phosphorus sulfide composition is in a powdery form.

[0398] [5a] A raw material composition for a sulfide-based inorganic solid electrolyte material, comprising the phosphorus sulfide composition according to any one of [1a] to [4a] above and lithium sulfide.

[0399] [6a] A method for producing a sulfide-based inorganic solid electrolyte material, comprising the step of mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material described in [5a].

[0400] [7a] A sulfide-based inorganic solid electrolyte material, wherein the sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained using the phosphorus sulfide composition described in any one of [1a] to [4a] as a raw material.

[0401] [8a] A sulfide-based inorganic solid electrolyte, comprising the sulfide-based inorganic solid electrolyte material described in [7a] above.

[0402] [9a] A sulfide-based inorganic solid electrolyte membrane, comprising the sulfide-based inorganic solid electrolyte described in [8a] above as a main component.

[0403] [10a] A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer comprises the sulfide-based inorganic solid electrolyte described in [7a] above.

[0404] [11a] A method for producing a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, the method comprising the step of sorting a phosphorus sulfide composition having a reactivity of 5.0°C / min or more as measured by the following [Method 1].

[0405] [Method 1]

[0406] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0407] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0408] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0409] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0410] The reactivity is derived from the following formula (1).

[0411] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0412] [12a] A quality control method for a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, the quality control method comprising the step of judging as acceptable a phosphorus sulfide composition having a reactivity of 5.0°C / min or more as measured by the following [Method 1].

[0413] [Method 1]

[0414] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0415] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0416] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0417] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0418] The reactivity is derived from the following formula (1).

[0419] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0420] The present invention can also be implemented in the following manners.

[0421] [1b] A method for producing a sulfide-based inorganic solid electrolyte material, wherein the method comprises: a step of mixing a raw material composition containing lithium sulfide and a phosphorus sulfide composition having a reactivity of 5.0°C / min or more as measured by the following [method 1] to obtain a mixture; and a step of subjecting the obtained mixture to a mechanochemical treatment to obtain a mechanochemically treated product.

[0422] [Method 1]

[0423] First, the phosphorus sulfide composition was pulverized in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and 10 g or more of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder.

[0424] Next, 25 mL of 2-propanol dried over molecular sieve 3A 1 / 16 for more than 24 hours was placed in a 100 mL tall beaker, and stirred at 20° C. and 200 rpm, and the entire amount of the test powder was added to the tall beaker.

[0425] The time when all the test powders are added is defined as measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as measurement start temperature Tm0.

[0426] The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max .

[0427] The reactivity is derived from the following formula (1).

[0428] Reactivity = (Tm max -Tm0) / (T max -T0)(1)

[0429] [2b] The method for producing a sulfide-based inorganic solid electrolyte material as described in [1b] above, wherein the phosphorus sulfide composition contains P2S5.

[0430] [3b] The method for producing a sulfide-based inorganic solid electrolyte material as described in [2b] above, wherein the content of the P2S5 in the phosphorus sulfide composition is 95% by mass or more.

[0431] [4b] A method for producing a sulfide-based inorganic solid electrolyte material as described in any one of [1b] to [3b] above, wherein the method further comprises a step of heat treating the mechanochemically treated product at a temperature in the range of 180°C to less than 450°C.

[0432] [5b] The method for producing a sulfide-based inorganic solid electrolyte material according to any one of [1b] to [4b] above, wherein the method does not include a step of heating the mechanochemically treated product at 450° C. or higher.

[0433] [6b] The method for producing a sulfide-based inorganic solid electrolyte material according to any one of [1b] to [5b], wherein the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in the following <Measurement of lithium ion conductivity> is 1.0×10 -3 S / cm or more.

[0434] <Measurement of lithium ion conductivity>

[0435] First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1 mm.

[0436] Then, the lithium ion conductivity of the obtained disk-shaped sample was measured by an electrochemical measuring apparatus under the conditions of an applied voltage of 10 mV, a measuring frequency range of 0.1 Hz to 3 MHz, and a measuring temperature of 27° C., using a Li foil as an electrode, and an AC impedance method.

[0437] [7b] The method for producing a sulfide-based inorganic solid electrolyte material according to any one of [1b] to [6b], wherein the oxidative decomposition current value of the sulfide-based inorganic solid electrolyte material measured by the method described in the following <Measurement of the maximum value of oxidative decomposition current> is 0.10×10 -5 mA or less.

[0438] <Determination of the maximum value of the oxidative decomposition current>

[0439] First, 150 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1.3 mm.

[0440] Then, a Li foil as a reference electrode / counter electrode was pressure-bonded to one surface of the obtained disk-shaped sample under the conditions of 18 MPa for 10 minutes, and then a SUS314 foil as a working electrode was attached to the other surface facing upward.

[0441] Then, using an electrochemical measuring apparatus, the maximum value of the oxidative decomposition current of the obtained particles was measured under the conditions of a sweep voltage range of 0 to 10 V, a voltage sweep rate of 5 mV / sec, and a measurement temperature of 25°C.

[0442] [8b] A method for producing a sulfide-based inorganic solid electrolyte material as described in any one of [1b] to [7b] above, wherein, in an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material obtained by the method described in the following <X-ray diffraction analysis>, there is no peak in the range of 2θ=27.70±0.50°, there is a peak in the range of 2θ=17.90±0.20°, there is a peak in the range of 2θ=29.00±0.50°, and there is a peak in the range of 2θ=29.75±0.25°.

[0443] <X-ray diffraction analysis>

[0444] An X-ray diffraction apparatus was used, with a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a divergence slit longitudinal limit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, and a measurement end angle of 90°. CuKα rays were used as the ray source to obtain an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material.

[0445] [9b] A method for producing a sulfide-based inorganic solid electrolyte material as described in any one of [1b] to [8b] above, wherein the sulfide-based inorganic solid electrolyte material contains Li3PS4.

[0446] [10b] A method for producing a sulfide-based inorganic solid electrolyte material as described in [9b] ​​above, wherein the above-mentioned Li3PS4 is α-type Li3PS4.

[0447] [11b] A sulfide-based inorganic solid electrolyte material, wherein the sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained by the method for producing a sulfide-based inorganic solid electrolyte material described in any one of [1b] to [10b] above.

[0448] [12b] A sulfide-based inorganic solid electrolyte, wherein the sulfide-based inorganic solid electrolyte comprises the sulfide-based inorganic solid electrolyte material described in [11b] above.

[0449] [13b] A sulfide-based inorganic solid electrolyte membrane, comprising the sulfide-based inorganic solid electrolyte described in [12b] above as a main component.

[0450] [14b] A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer comprises the sulfide-based inorganic solid electrolyte material described in [11b] above.

[0451] The present invention can also be implemented in the following manners.

[0452] [1c] A sulfide-based inorganic solid electrolyte material, which is a sulfide-based inorganic solid electrolyte material containing Li, P and S as constituent elements, wherein, in an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material obtained by the method described in the following <X-ray diffraction analysis>, there is no peak in the range of 2θ=27.70±0.50°, there is a peak in the range of 2θ=17.90±0.20°, there is a peak in the range of 2θ=29.00±0.50°, and there is a peak in the range of 2θ=29.75±0.25°.

[0453] <X-ray diffraction analysis>

[0454] An X-ray diffraction apparatus was used with a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a divergence slit longitudinal limit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, and a measurement end angle of 90°. CuKα rays were used as the ray source. In addition, a glass sample plate was used as the sample holder to obtain an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material.

[0455] [2c] The sulfide-based inorganic solid electrolyte material as described in [1c] above, wherein the sulfide-based inorganic solid electrolyte material contains Li3PS4.

[0456] [3c] The sulfide-based inorganic solid electrolyte material as described in [2c] above, wherein the content of the above-mentioned Li3PS4 is 95% by mass or more.

[0457] [4c] The sulfide-based inorganic solid electrolyte material according to any one of [1c] to [3c], wherein the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in the following <Measurement of lithium ion conductivity> is 1.0×10 -3 S / cm or more.

[0458] <Measurement of lithium ion conductivity>

[0459] First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1 mm.

[0460] Then, the lithium ion conductivity of the obtained disk-shaped sample was measured by an electrochemical measuring apparatus under the conditions of an applied voltage of 10 mV, a measuring frequency range of 0.1 Hz to 3 MHz, and a measuring temperature of 27° C., using a Li foil as an electrode, and an AC impedance method.

[0461] [5c] The sulfide-based inorganic solid electrolyte material according to any one of [1c] to [4c], wherein the oxidative decomposition current value of the sulfide-based inorganic solid electrolyte material measured by the method described in <Measurement of the maximum value of oxidative decomposition current> is 0.10×10 -5 mA or less.

[0462] <Determination of the maximum value of the oxidative decomposition current>

[0463] First, 150 mg of the sulfide-based inorganic solid electrolyte material was pressurized under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1.3 mm.

[0464] Then, a Li foil as a reference electrode / counter electrode was pressure-bonded to one surface of the obtained disk-shaped sample under the conditions of 18 MPa for 10 minutes, and then a SUS314 foil as a working electrode was attached to the other surface facing upward.

[0465] Then, using an electrochemical measuring apparatus, the maximum value of the oxidative decomposition current of the obtained particles was measured under the conditions of a sweep voltage range of 0 to 10 V, a voltage sweep rate of 5 mV / sec, and a measurement temperature of 25°C.

[0466] [6c] A sulfide-based inorganic solid electrolyte, comprising the sulfide-based inorganic solid electrolyte material according to any one of [1c] to [5c] above.

[0467] [7c] A sulfide-based inorganic solid electrolyte membrane, comprising the sulfide-based inorganic solid electrolyte described in [6c] above as a main component.

[0468] [8c] A lithium-ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer comprises the sulfide-based inorganic solid electrolyte material described in any one of [1c] to [5c].

[0469] Description of Reference Numerals

[0470] 100: Lithium-ion battery.

[0471] 101: Positive electrode active material layer.

[0472] 103: Negative electrode active material layer.

[0473] 105: Current collector.

[0474] 110: Positive electrode.

[0475] 120: Electrolyte layer.

[0476] 130: Negative pole.

Claims

1. A phosphorus sulfide composition, which is a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, wherein: The reactivity of the phosphorus sulfide composition measured by the following method 1 is 5.0°C / min or more, Method 1: First, the phosphorus sulfide composition was crushed in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and more than 10 g of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder. Then, 25 mL of 2-propanol dried for more than 24 hours using a molecular sieve 3A 1 / 16 was placed in a 100 mL tall beaker and stirred at 20°C and 200 rpm. The entire amount of the test powder was added to the tall beaker. The time when all the test powder is added is defined as the measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as the measurement start temperature Tm0. The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max , The reactivity is derived from the following formula (1): Reactivity = (Tm max -Tm0) / (T max -T0)(1).

2. The phosphorus sulfide composition according to claim 1, wherein The phosphorus sulfide composition contains P2S5.

3. The phosphorus sulfide composition according to claim 2, wherein The content of P2S5 in the phosphorus sulfide composition is 95 mass % or more.

4. The phosphorus sulfide composition according to any one of claims 1 to 3, wherein The phosphorus sulfide composition is in powder form.

5. A raw material composition of a sulfide-based inorganic solid electrolyte material, wherein: The raw material composition of the sulfide-based inorganic solid electrolyte material comprises the phosphorus sulfide composition according to any one of claims 1 to 4 and lithium sulfide.

6. A method for producing a sulfide-based inorganic solid electrolyte material, wherein: The production method includes the step of mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material according to claim 5 . 7 . A sulfide-based inorganic solid electrolyte material, wherein the sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained by using the phosphorus sulfide composition according to any one of claims 1 to 4 as a raw material.

8. A sulfide-based inorganic solid electrolyte, wherein: The sulfide-based inorganic solid electrolyte comprises the sulfide-based inorganic solid electrolyte material according to claim 7 .

9. A sulfide-based inorganic solid electrolyte membrane, wherein: The sulfide-based inorganic solid electrolyte membrane contains the sulfide-based inorganic solid electrolyte according to claim 8 as a main component.

10. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material according to claim 7 .

11. A method for producing a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, wherein: The production method comprises the step of sorting a phosphorus sulfide composition having a reactivity of 5.0° C. / min or more measured by the following method 1, Method 1: First, the phosphorus sulfide composition was crushed in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and more than 10 g of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder. Then, 25 mL of 2-propanol dried for more than 24 hours using a molecular sieve 3A 1 / 16 was placed in a 100 mL tall beaker and stirred at 20°C and 200 rpm. The entire amount of the test powder was added to the tall beaker. The time when all the test powder is added is defined as the measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as the measurement start temperature Tm0. The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max , The reactivity is derived from the following formula (1): Reactivity = (Tm max -Tm0) / (T max -T0)(1).

12. A method for quality management of a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material, wherein: The quality management method includes the step of judging a phosphorus sulfide composition having a reactivity of 5.0° C. / min or more measured by the following method 1 as acceptable, Method 1: First, the phosphorus sulfide composition was crushed in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and more than 10 g of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder. Then, 25 mL of 2-propanol dried for more than 24 hours using a molecular sieve 3A 1 / 16 was placed in a 100 mL tall beaker and stirred at 20°C and 200 rpm. The entire amount of the test powder was added to the tall beaker. The time when all the test powder is added is defined as the measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as the measurement start temperature Tm0. The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max , The reactivity is derived from the following formula (1): Reactivity = (Tm max -Tm0) / (T max -T0)(1).

13. A method for producing a sulfide-based inorganic solid electrolyte material, wherein: The manufacturing method comprises: a step of mixing a raw material composition containing lithium sulfide and the phosphorus sulfide composition according to any one of claims 1 to 4 to obtain a mixture; and a step of subjecting the obtained mixture to a mechanochemical treatment to obtain a mechanochemically treated product, Method 1: First, the phosphorus sulfide composition was crushed in an agate mortar in an argon atmosphere, and after being classified through a sieve with a mesh size of 500 μm, the undersize fraction was classified through a sieve with a mesh size of 250 μm, and more than 10 g of the oversize fraction was recovered. Of the recovered powder, 9.20 g was accurately weighed as a test powder. Then, 25 mL of 2-propanol dried for more than 24 hours using a molecular sieve 3A 1 / 16 was placed in a 100 mL tall beaker and stirred at 20°C and 200 rpm. The entire amount of the test powder was added to the tall beaker. The time when all the test powder is added is defined as the measurement start time T0, and the temperature of the liquid in the tall beaker is measured at intervals of 2 seconds from T0. The temperature of the liquid in the tall beaker measured at T0 is defined as the measurement start temperature Tm0. The time when the temperature of the liquid in the tall beaker stops rising is defined as the maximum temperature reaching time T. max , will be in T max The temperature of the liquid in the tall beaker is measured as the maximum temperature Tm. max , The reactivity is derived from the following formula (1): Reactivity = (Tm max -Tm0) / (T max -T0)(1).

14. The method for producing a sulfide-based inorganic solid electrolyte material according to claim 13, wherein: The manufacturing method further includes a step of heat treating the mechanochemically treated product at a temperature in a range of 180° C. to less than 450° C.

15. The method for producing a sulfide-based inorganic solid electrolyte material according to claim 13 or 14, wherein: The manufacturing method does not include a step of heating the mechanochemically treated product at 450° C. or higher.

16. The method for producing a sulfide-based inorganic solid electrolyte material according to any one of claims 13 to 15, wherein: The lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in the following measurement of lithium ion conductivity is 1.0×10 -3 S / cm or more, Determination of lithium ion conductivity: First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressurized at 270 MPa for 10 minutes to obtain a disk-shaped sample with a diameter of 9.5 mm and a thickness of 1 mm. Then, the lithium ion conductivity of the obtained disk-shaped sample was measured by an electrochemical measuring apparatus under the conditions of an applied voltage of 10 mV, a measuring frequency range of 0.1 Hz to 3 MHz, and a measuring temperature of 27° C., using a Li foil as an electrode, and an AC impedance method.

17. The method for producing a sulfide-based inorganic solid electrolyte material according to any one of claims 13 to 16, wherein: The oxidation decomposition current value of the sulfide-based inorganic solid electrolyte material measured by the method described in the following determination of the maximum value of oxidation decomposition current is 0.10×10 -5 mA or less, Determination of the maximum value of the oxidative decomposition current: First, 150 mg of the sulfide-based inorganic solid electrolyte material was pressurized at 270 MPa for 10 minutes to obtain a disk-shaped sample with a diameter of 9.5 mm and a thickness of 1.3 mm. Then, a Li foil as a reference electrode / counter electrode was pressed onto one surface of the obtained disc-shaped sample under the conditions of 18 MPa for 10 minutes, and then a SUS314 foil as a working electrode was attached to the other surface facing upward. Then, using an electrochemical measuring apparatus, the maximum value of the oxidative decomposition current of the obtained particles was measured under the conditions of a sweep voltage range of 0 to 10 V, a voltage sweep rate of 5 mV / sec, and a measurement temperature of 25°C.

18. The method for producing a sulfide-based inorganic solid electrolyte material according to any one of claims 13 to 17, wherein: In the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material obtained by the method described in the following X-ray diffraction analysis, There is no peak in the range of 2θ = 27.70 ± 0.50°, There is a peak in the range of 2θ=17.90±0.20°, There is a peak in the range of 2θ=29.00±0.50°, There is a peak in the range of 2θ = 29.75 ± 0.25°, X-ray diffraction analysis: An X-ray diffraction apparatus was used, with a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a divergence slit longitudinal limit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, and a measurement end angle of 90°. CuKα rays were used as the ray source to obtain an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material.

19. The method for producing a sulfide-based inorganic solid electrolyte material according to any one of claims 13 to 18, wherein: The sulfide-based inorganic solid electrolyte material includes Li3PS4.

20. The method for producing a sulfide-based inorganic solid electrolyte material according to claim 19, wherein: The Li3PS4 is α-type Li3PS4. 21 . A sulfide-based inorganic solid electrolyte material, wherein the sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained by the method for producing a sulfide-based inorganic solid electrolyte material according to any one of claims 13 to 20.

22. A sulfide-based inorganic solid electrolyte, wherein: The sulfide-based inorganic solid electrolyte comprises the sulfide-based inorganic solid electrolyte material according to claim 21 .

23. A sulfide-based inorganic solid electrolyte membrane, wherein: The sulfide-based inorganic solid electrolyte membrane contains the sulfide-based inorganic solid electrolyte according to claim 22 as a main component.

24. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material according to claim 21 .

25. A sulfide-based inorganic solid electrolyte material, comprising Li, P and S as constituent elements, wherein: In the X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material obtained by the method described in the following X-ray diffraction analysis, There is no peak in the range of 2θ = 27.70 ± 0.50°, There is a peak in the range of 2θ=17.90±0.20°, There is a peak in the range of 2θ=29.00±0.50°, There is a peak in the range of 2θ = 29.75 ± 0.25°, X-ray diffraction analysis: An X-ray diffraction apparatus was used with a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a divergence slit longitudinal limit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, and a measurement end angle of 90°. CuKα rays were used as the ray source. In addition, a glass sample plate was used as the sample holder to obtain an X-ray diffraction analysis spectrum of the sulfide-based inorganic solid electrolyte material.

26. The sulfide-based inorganic solid electrolyte material according to claim 25, wherein The sulfide-based inorganic solid electrolyte material includes Li3PS4.

27. The sulfide-based inorganic solid electrolyte material according to claim 26, wherein The content of Li3PS4 is greater than 95 mass %.

28. The sulfide-based inorganic solid electrolyte material according to any one of claims 25 to 27, wherein The lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in the following measurement of lithium ion conductivity is 1.0×10 -3 S / cm or more, Determination of lithium ion conductivity: First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressurized at 270 MPa for 10 minutes to obtain a disk-shaped sample with a diameter of 9.5 mm and a thickness of 1 mm. Then, the lithium ion conductivity of the obtained disk-shaped sample was measured by an electrochemical measuring apparatus under the conditions of an applied voltage of 10 mV, a measuring frequency range of 0.1 Hz to 3 MHz, and a measuring temperature of 27° C., using a Li foil as an electrode, and an AC impedance method.

29. The sulfide-based inorganic solid electrolyte material according to any one of claims 25 to 28, wherein The oxidation decomposition current value of the sulfide-based inorganic solid electrolyte material measured by the method described in the following determination of the maximum value of oxidation decomposition current is 0.10×10 -5 mA or less, Determination of the maximum value of the oxidative decomposition current: First, 150 mg of the sulfide-based inorganic solid electrolyte material was pressurized at 270 MPa for 10 minutes to obtain a disk-shaped sample with a diameter of 9.5 mm and a thickness of 1.3 mm. Then, a Li foil as a reference electrode / counter electrode was pressed onto one surface of the obtained disc-shaped sample under the conditions of 18 MPa for 10 minutes, and then a SUS314 foil as a working electrode was attached to the other surface facing upward. Then, using an electrochemical measuring apparatus, the maximum value of the oxidative decomposition current of the obtained particles was measured under the conditions of a sweep voltage range of 0 to 10 V, a voltage sweep rate of 5 mV / sec, and a measurement temperature of 25°C.

30. A sulfide-based inorganic solid electrolyte, wherein: The sulfide-based inorganic solid electrolyte includes the sulfide-based inorganic solid electrolyte material according to any one of claims 25 to 29.

31. A sulfide-based inorganic solid electrolyte membrane, wherein: The sulfide-based inorganic solid electrolyte membrane contains the sulfide-based inorganic solid electrolyte according to claim 30 as a main component.

32. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material according to any one of claims 25 to 29.

Citation Information

Patent Citations

  • Reaction treatment method, reaction treatment device, and reaction treatment container

    JP2022128495A

  • Information processing device, moving body, photographing system, photographing control method and program

    JP2022128496A

  • Systems and methods for analyzing analytes extracted from samples using adsorbent materials - Patents.com

    JP2022128497A